The Image of the Sea in Mikalojus Konstantinas Čiurlionis’s and Vydūnas’s Artistic Program of the Creation of the World - Martišiūtė-Linartienė, Aušra (Colloquia, 2021)
The article illustrates the creative connections between the composer and painter Mikalojus Konstantinas Čiurlionis (1875-1911) and the playwright and philosopher Vydūnas (Vilhelmas Storostas, 1868-1953) observed and described by their contemporaries and later, by scholars in a very general way. The article discusses the following elements of Čiurlionis’s and Vydūnas’s creative program: a work of art as a vision, the creative act as the creation of one’s own world, the principle of combining abstract and specific, and the positivity of worldview expressed in the direction of ascent. The image of the sea, which has become the main object of the work, expresses the creative world. In the interpretations of the legend about Jūratė and Kastytis, the significance of love between the human and the goddess alters from human humility and mutual feeling of love to the meanings of co-creation revealed by Čiurlionis and Vydūnas, depicting the reaction of the gods to the love of the goddess and man—from the punishment to blessing (Vydūnas’s Jūraitė). Interpretations of the legend vary from the “bound” Prometheus—the image of Kastytis bound to a rock to the meanings of the liberated Prometheus (looking at the corpus of Čiurlionis’s works, the painting “Rex,” the finale of Vydūnas’s Jūrų varpai and Jūraitė assert the liberation of the human-creator). Both artists affirm the strengthening of the inner powers of the individual. They consolidate the unmatched value of the power of human creativity.
Keywords: Mikalojus Konstantinas Čiurlionis; Vydūnas; vision; image of the sea; the myth of Prometheus